THE TERM SYSTEM "FORMS OF ENTREPRENEURIAL ACTIVITY" IN ENGLISH AND RUSSIAN AND METHODS OF ITS TRANSLATION - Raxmonova Sardora Muminjonovna (Journals Park Publishing, 2022)
The article provides a comparative analysis of the forms of entrepreneurial activity in the Russian and Anglo-American systems of law; reveals significant differences in the volumes of meanings of legal concepts in two languages, provides translation recommendations. In a contrastive way, the terms that are used to describe such subject areas as: various forms of entrepreneurial activity, the constituent documents of the company are considered. It is noted that the greatest problems for translation and understanding of the text are caused by non-equivalent and partially equivalent vocabulary.
Keywords: legal terminology; comparative analysis; partially equivalent vocabulary